Pengetahuan dan Perilaku Remaja dalam Pencegahan Anemia di Pesantren Kota Jambi - Fatmawati, Tina Yuli; Jeki, Andicha Gustra; Efni, Nel; Ariyanto, Ariyanto (Jurnal Akademika Baiturrahim Jambi, 2025)
The most frequently encountered nutritional problem in adolescents is anemia. The prevalence of anemia in Indonesia in women aged 15-24 years is 84.6%. Adolescent girls are more vulnerable than adolescent boys. This is because the need for iron in teenage girls who are menstruating is three times greater than that of boys. The aim of this research is to describe the knowledge and behavior of adolescents in preventing anemia at the Al Hidayah Islamic Boarding School, Jambi City. This research is descriptive research conducted to determine the description of adolescent knowledge and behavior in preventing anemia. This research took place at the Al Hidayah Islamic Boarding School, Jambi City with a sample size of 94 young women. The research instrument used was a questionnaire. Next, the data was analyzed using univariate analysis to get an idea of the frequency distribution of all the variables studied. The research results showed that the largest age distribution of respondents was 15 and 16 years old (34%), the highest class distribution of respondents was in class Anemia prevention behavior: The majority of respondents had poor behavior, 83 respondents (88.3%). It is recommended that schools improve facilities that support increasing knowledge about anemia among young women. This can be done by holding routine counseling every semester or checking hemoglobin (Hb) levels periodically